Performance of the new reinforcement system in the increase of shear strength of typical geogrid interface with soil. Issue 3 (June 2016) - Mosallanezhad, M.; Alfaro, M.C.; Hataf, N.; Sadat Taghavi, S.H.
Abstract: In recent years, the study of the shear strength of soil with geosynthetics has caught the attention of scholars. In this study, by changing the traditional geogrid structure and adding polymeric anchors to the reinforcement grid, naming it Grid–Anchor (G–A), it is sought to experimentally analyze the performance of this new system by increasing the Coefficient of Interaction Ratio in Direct Shear (CIRDS ). To achieve this, 16 large-scale direct shear tests were conducted on a typical geogrid and G–A system. The results of this showed that CIRDS is, on average, 1.45 times greater. In other words, the interaction between soil and the reinforcement in G–A system increases by almost 50% compared to that of typical geogrid regarding direct shear mechanism.